Pengaruh Gel Lidah Buaya Terhadap Pertumbuhan Stek Bangun-Bangun (Plectranthus amboinicus) - Husniatunnisa, Husniatunnisa; Arwita, Widya; Nurkhofifah, Indah; Sastra, Siti Fathiya Dwinda (Journal of Natural Sciences, 2025)
Bangun-bangun (Plectranthus amboinicus) is a herbal plant that is widely used as a lactagogum to increase breast milk production. However, the propagation of this plant still faces obstacles, especially in the process of stem cuttings that require the support of growth stimulants. Aloe vera is known to contain growth hormones such as auxin and gibberellin which have the potential to increase the success of plant cuttings. This study aims to analyze the effect of giving aloe vera gel on the growth of bangun-bangun plant cuttings. The research method used is a qualitative approach with direct observation of the growth of bangun-bangun plant cuttings treated with aloe vera gel with various concentrations. The data collected included root length, number of shoots, number of leaves, and cutting viability. The results showed that giving aloe vera gel had a significant effect on cutting growth. Certain concentrations of aloe vera gel can increase the percentage of successful cuttings, accelerate root formation, and increase the number of shoots and leaves compared to cuttings that are not given treatment. The mechanism of action of active compounds in aloe vera that play a role in stimulating root and shoot growth, as well as environmental factors that also affect the effectiveness of the treatment. The results of this study provide implications for the vegetative propagation of bangun-bangun plants and can be a natural alternative in supporting the cultivation of herbal plants.